The Tunisian Law on public funding of associations: study and translation - Pérez Beltrán, Carmelo (Anaquel de Estudios Árabes, 2018)
Study and translation from Arabic into Spanish of the current Tunisian Law on public funding of associations. In the first part of the article this legislation is set within the framework of legal reforms implemented in Tunisia after the outbreak of the social revolts in 2010-2011. Then, some aspects of the Law regarding specific conditions and types of public funding, bestowal procedures, monitoring and control of public funds, etc. are analysed in deep. In the second part, an Spanish translation of the original Arabic text of the Law published in the Official Gazette of the Tunisian Republic is proposed.